Igneous Rock Associations 4. Oceanic Island Volcanism I Mineralogy and Petrology - Greenough, John; Dostal, Jaroslav; Mallory-Greenough, Leanne (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2005)
SUMMARY Oceanic islands tend to occur at the young ends of hotspot trails because they record the passage of oceanic plates over rising convection cells (plumes) in the mantle, or the propagation of cracks in the lithosphere. Basaltic volcanism on oceanic islands is generally unexplosive and, although potentially destructive, poses less threat to human life than volcanism in other tectonic environments. However, the possibility of giant tsunamis from the catastrophic gravitational collapse of islands is of real concern for major cities surrounding the ocean basins. Two series of magmas are recognized in oceanic islands. Tholeiites form at lower pressures than alkali basalts, from higher percentages of decompression melting. The former contain a low-Ca pyroxene and the latter can crystallize nepheline. Furthermore, minerals common to both series (chromite, olivine, augite, plagioclase, magnetite and ilmenite) are compositionally distinct reflecting fundamental chemical differences between the two magma series. Mineral compositions vary as magmas evolve in sub-volcanic, lithospheric magma chambers by assimilation and differentiation. Magmas assimilate wall rocks in these chambers. Time-scales for differentiation (mostly crystal fractionation) are generally less than a few thousand years. Early olivine, pyroxene, chromite and immiscible sulfide formation cause compatible elements (e.g., Ni, Co, Cr) to decline rapidly as differentiation proceeds. Plagioclase dramatically removes Sr at intermediate stages and alkali feldspars sequester Ba and Rb as late-stage trachytes and phonolites form in alkaline magmas. The high-field-strength elements are generally incompatible but locally decline reflecting apatite (P) and Fe-Ti oxide (Ti, Nb, Ta) removal. Studies of layering in individual lava flows suggest that rising volatiles may effect mass transfer of complexed ions during differentiation in magma chambers.